2021
DOI: 10.3390/cancers13081791
|View full text |Cite
|
Sign up to set email alerts
|

MR-Guided Hypofractionated Radiotherapy: Current Emerging Data and Promising Perspectives for Localized Prostate Cancer

Abstract: In this review we summarize the currently available evidence about the role of hybrid machines for MR-guided radiotherapy for prostate stereotactic body radiotherapy. Given the novelty of this technology, to date few data are accessible, but they all report very promising results in terms of tolerability and preliminary clinical outcomes. Most of the studies highlight the favorable impact of on-board magnetic resonance imaging as a means to improve target and organs at risk identification with a consequent adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 90 publications
0
24
0
Order By: Relevance
“…Prostate cancer (PC) is one of the major diseases thought to be greatly benefited by oMRgART (Pathmanathan et al 2018 ; Cuccia et al 2021 ; Tocco et al 2020 ). It is also one of the most treated targets by both 0.35T and 1.5T MRgRT, particularly in the form of ultrahypofractionation, also known as stereotactic body radiotherapy (SBRT) (Ugurluer et al 2021 ; Tetar et al 2021 ; Bruynzeel et al 2019 ; Otterloo et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PC) is one of the major diseases thought to be greatly benefited by oMRgART (Pathmanathan et al 2018 ; Cuccia et al 2021 ; Tocco et al 2020 ). It is also one of the most treated targets by both 0.35T and 1.5T MRgRT, particularly in the form of ultrahypofractionation, also known as stereotactic body radiotherapy (SBRT) (Ugurluer et al 2021 ; Tetar et al 2021 ; Bruynzeel et al 2019 ; Otterloo et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 19 The MR-Linac also allows therapy in fewer sessions with a higher dose of radiation therapy, also called hypofractionation, hence, permitting a shorter treatment. 20 , 21 This can be beneficial in a case like localized prostate cancer 22 , 23 , 24 because traditional external beam radiation therapy often varies from 5, 20, to 39 treatment sessions. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported feasibility and early clinical outcome of delivering adaptive radiotherapy for prostate cancer on the MRL [9] , [10] , [11] . However, there are two major factors in the existing configuration of the MRL that could limit the potential of MR-guided adaptive radiotherapy: 1) Longer treatment session due to the need for recontouring, re-optimization and delivery using IMRT [12] , [13] , [14] , [15] and 2) Inferior plan quality by IMRT when compared to Volumetric Modulated Arc Therapy (VMAT) [14] , [16] .…”
Section: Introductionmentioning
confidence: 99%